2016
DOI: 10.1080/00140139.2016.1165870
|View full text |Cite
|
Sign up to set email alerts
|

What is a ‘good’ job? Modelling job quality for blue collar workers

Abstract: This paper proposes a model of job quality, developed from interviews with blue collar workers: bus drivers, manufacturing operatives and cleaners (n=80). The model distinguishes between core features, important for almost all workers, and 'job fit' features, important to some but not others, or where individuals might have different preferences. Core job features found important for almost all interviewees included job security, personal safety, and having enough pay to meet their needs. 'Job fit' features in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
(45 reference statements)
3
26
0
1
Order By: Relevance
“…Although different job characteristics may be more or less important for well-being depending on context and individual circumstances (Jones, Haslam, and Haslam 2017), there is consistent evidence from observational studies (i.e. nonintervention studies that assess naturally occurring levels of job characteristics) to indicate that job characteristics need to be compatible with other organisational processes and sub-systems (Cherns 1987;Clegg 2000;Davis et al 2013).…”
Section: Job Design and Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…Although different job characteristics may be more or less important for well-being depending on context and individual circumstances (Jones, Haslam, and Haslam 2017), there is consistent evidence from observational studies (i.e. nonintervention studies that assess naturally occurring levels of job characteristics) to indicate that job characteristics need to be compatible with other organisational processes and sub-systems (Cherns 1987;Clegg 2000;Davis et al 2013).…”
Section: Job Design and Well-beingmentioning
confidence: 99%
“…There is long-standing and continuing interest in psychological well-being and the quality of jobs in work organisations (Grote and Guest 2017;Jones, Haslam, and Haslam 2017). The provision of high quality jobs is seen as a key lever in improving well-being in political circles (All Parliamentary Work Group on Wellbeing Economics 2014) and across a broad range of stakeholders including the general public, trades union officials, employment specialists, managers and students (Daniels et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a need for research addressing the challenge identified by Straker and Mathiassen (2009): increasing physical activity through the way work is organised and done. We need to understand how to design jobs that are productive, safe and fulfilling, whilst also being good for health, integrating rather than eliminating physical activity and mental demands (Jones, Haslam, and Haslam 2016). Ergonomics endeavours to publish high quality papers, reporting research that makes a substantive contribution to contemporary science and articles which have an impact on ergonomics practice or debate.…”
Section: Authors Titlementioning
confidence: 99%
“…That idea of 'good work' needs to be self-defined by individuals themselves so that job roles are tailored to their specific needs (both health and wider) and interests, alongside a set of employment characteristics that are shared more generally across all individuals (e.g. contractual and income security, income adequacy, choice and agency, interest, safety, respect, opportunities for development) (Ritter and Anker, 2002;Warhurst et al, 2012;Jones et al, 2017).…”
Section: Introductionmentioning
confidence: 99%